Britain's economic miracle : myth or reality? - Healey, Nige (Routledge, 1993)
Recent years have witnessed radical changes in British economic policy. However, the recession of the early nineties has cast doubts about whether these were successful. The much heralded economic miracle is now much tarnished. This book offers a timely and comprehensive non-technical throughout it analyses the basis of policy making as well as discussing its impact on economic performance.